Fodder quality variation in Grewia laevigata Vahl. in Himachal Pradesh - Mariappan, N.; Sankhyan, H.P.; Gurunathan, N. (Indian Journal of Agroforestry, 2020)
The present study on fodder quality variation in Grewia laevigata Vahl. in Himachal Pradesh revealed that some of the traits viz., leaf fresh weight (g), leaf dry weight (g), leaf dry matter (%), crude protein (%), crude fibre (%), ether extract (%), total ash (%) and nitrogen free extract (%) exhibited variation between the sites. There were also significant differences between trees within the locality in almost all the parameters including the nitrogen free extract and dry matter content in Grewia laevigata. In simple correlation combinations, positive and negative significant variations were exhibited. Genotypic correlation coefficients were found greater than phenotypic one for almost all the leaf fodder traits.